Effects of Dissolved Organic Carbon, Ultraviolet Light and their Co‐Exposure on Deepwater Horizon crude oil acute toxicity to larval red drum (Sciaenops ocellatus). (26th October 2020) - Bonatesta, Fabrizio; Leads, Rachel R; Price, Edwin R.; Roberts, Aaron P.; Mager, Edward M.
Abstract: In the aquatic environment, ubiquitous natural factors such as ultraviolet light (UV) and dissolved organic carbon (DOC) are likely to influence crude oil toxicity. The present study examined the interactive effects of DOC, UV, and DOC–UV co‐exposure on the acute toxicity of Deepwater Horizon crude oil in larval red drum ( Sciaenops ocellatus ). Although DOC alone did not influence crude oil toxicity, it mildly reduced UV photo‐enhanced toxicity. Environ Toxicol Chem 2020;39:2509–2515. © 2020 SETAC Abstract : Emulating environmental conditions in a laboratory setting: ultraviolet (UV), dissolved organic carbon (DOC), and crude oil co‐exposure to Sicaenops ocellatus . Although DOC alone did not influence acute crude oil toxicity, it mildly reduced the UV photo‐enhanced toxicity of crude oil.